Museums in the Pandemic: A Survey of Responses on the Current Crisis. Issue 1 (1st July 2020) - Cobley, Joanna; Gaimster, David; So, Stephanie; Gorbey, Ken; Arnold, Ken; Poulot, Dominique; Soares, Bruno Brulon; Morse, Nuala; Osorio Sunnucks, Laura; Martínez Milantchí, María de las Mercedes; Serrano, Alberto; Lehrer, Erica; et al.
Abstract : Throughout human history, the spread of disease has closed borders, restricted civic movement, and fueled fear of the unknown; yet at the same time, it has helped build cultural resilience. On 11 March 2020 the World Health Organization (WHO) classified COVID-19 as a pandemic. The novel zoonotic disease, first reported to the WHO in December 2019, was no longer restricted to Wuhan or to China, as the highly contagious coronavirus had spread to more than 60 countries. The public health message to citizens everywhere was to save lives by staying home; the economic fallout stemming from this sudden rupture of services and the impact on people's well-being was mindboggling. Around the globe museums, galleries, and popular world heritage sites closed (Associated Press 2020 ). The Smithsonian Magazine reported that all 19 institutes, including the National Zoo and the National Museum of the American Indian (NMAI), would be closed to the public on 14 March (Daher 2020 ). On the same day, New Zealand's borders closed, and the tourism industry, so reliant on international visitors, choked. Museums previously deemed safe havens of society and culture became petri dishes to avoid; local museums first removed toys from their cafés and children's spaces, then the museum doors closed and staff worked from home. In some cases, front-of-the-house staff were redeployed to support back-of-the-house staff with cataloguing and digitization projects. You could smell fear everywhere.